Vitamin A Supplementation Coverage and Ocular Signs among Children Aged 6–59 Months in Aleta Chuko Woreda, Sidama Zone, Southern Ethiopia - Temesgen Nigusse; Achamyelesh Gebretsadik (Journal of Nutrition and Metabolism)
Background. Periodic vitamin A supplementation to children is a cost-effective strategy to avert vitamin A deficiency. However, few pieces of evidence are available about the coverage of vitamin A supplementation at the community level in the study area. Therefore, the aim of this study was to assess vitamin A supplementation coverage and prevalence of ocular signs of vitamin A deficiency among children aged 6–59 months. Methods. Community-based cross-sectional study design was conducted using a two-stage stratified random sampling method. Data were collected from mothers with children aged 6–59 months using a structured pretested questionnaire. A total of 665 children aged 6 to 59 months were examined for clinical signs and symptoms of vitamin A deficiency by trained clinical health professionals. Descriptive statistics and logistic regression were done. Result. Vitamin A supplementation coverage in the study area was 36.2% (95% CI: 32.6–39.9). Overall, the prevalence of xerophthalmia was 2.7%. Age group 6–23 months (AOR: 2.1, 95% CI: 1.4–2.9), good maternal knowledge (AOR: 1.5, 95% CI: 1.2–2.1), children with high wealth status (AOR: 2.3, 95% CI: 1.4–3.8), precampaign health education on vitamin A (AOR: 3.4,95% CI: 2.1–5.6), member of Health Development Army (AOR: 2.7, 95% CI: 1.7–4.2), and access to health facility within <30 minutes (AOR: 2.5, 95% CI: 1.6–3.8) were significantly associated with the receipt of vitamin A capsule. Conclusion. Vitamin A supplementation coverage of the study area was low as compared to the UNICEF threshold of 70%. Vitamin A deficiency is a public health problem in the study area. Increasing maternal level of knowledge, precampaign health education on vitamin A supplementation, and strengthening Health Development Army are recommended to increase the vitamin A supplementation coverage.